2019 57th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2019
DOI: 10.1109/allerton.2019.8919649
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Load Models on Equilibria, Stability and Algebraic Manifolds of Power System Differential-Algebraic System

Abstract: Load models have a great impact on voltage behaviors as well as power system transient dynamics. Extensive work has been done on this topic, proposing appropriate load models and capturing better load behaviors during transient. This paper presents a comprehensive study to investigate the geometric and topological changes induced by different load models for the traditional power system differential-algebraic equations. Specifically, we attempt to reveal the deformation of equilibria, stability regions, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…On the other hand, the singular surface 5 of algebraic constraints can also contribute to the dynamic instability phenomenon [41]- [43]. A comprehensive numerical study of singularity induced dynamic voltage instability can be found in [39], which is also confirmed in [40].…”
Section: A Dynamic Voltage Instabilitymentioning
confidence: 65%
See 4 more Smart Citations
“…On the other hand, the singular surface 5 of algebraic constraints can also contribute to the dynamic instability phenomenon [41]- [43]. A comprehensive numerical study of singularity induced dynamic voltage instability can be found in [39], which is also confirmed in [40].…”
Section: A Dynamic Voltage Instabilitymentioning
confidence: 65%
“…By choosing the center-of-inertial (COI) reference frame, [40] showed that the dynamic stability boundary of this example coincides with the singular surface, suggesting that any transient instability is caused by the singularity.…”
Section: A 9-bus Dynamic Voltage Instability Example -Distance In Act...mentioning
confidence: 90%
See 3 more Smart Citations